2013
DOI: 10.5152/tud.2013.016
|View full text |Cite
|
Sign up to set email alerts
|

Fetal urinoma and prenatal hydronephrosis: how is renal function affected?

Abstract: Objective: In our study, the functional prognosis of kidneys with prenatal urinomas were investigated. Material and methods:Between 2006 and 2010, fetal urinomas were detected in 19 fetuses using prenatal ultrasonography (US), and the medical records were reviewed retrospectively. Of the 19 cases, the follow-up data were available for 10 fetuses. The gestational age at diagnosis, prognosis of urinomas, clinical course and renal functions were recorded. Postnatal renal functions were assessed with renal scintig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Of these papers, 594 were excluded based on exclusion criteria. A total of 46 studies were ultimately included in the Bayesian meta‐analysis (Table ) 8,9,16–59 …”
Section: Resultsmentioning
confidence: 99%
“…Of these papers, 594 were excluded based on exclusion criteria. A total of 46 studies were ultimately included in the Bayesian meta‐analysis (Table ) 8,9,16–59 …”
Section: Resultsmentioning
confidence: 99%
“…[5,14,15] Prenatal urinoma related to UPJO generally is associated with poor functional prognosis of the affected kidney. [2,[16][17][18] Charcos et al collected from the literature from 1985 to 2013, 26 cases (including one own) of prenatal diagnosis of urinoma and UPJO -in almost all of them excluding one -minimal or no function of the kidney was found after birth. [2] The next 7 cases were published by Adorisio et al in 2011, [15] six by Oktar et al in 2013 [18] and nine by Yitta et al in 2014 [14] -also in those cases minimal or no function of the ipsilateral kidney with UPJO and urinoma were noted in surviving patients.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal normal kidney function in UPJHN cases affected by ipsilateral urinoma is only 7% (28,29). Another study reported that the prognosis is more morbid in the presence of urinoma with prenatal UPJHN than other urinary tract obstructions (11).…”
Section: Other Urinary System Ultrasound Findings In Prenatal Upjhnmentioning
confidence: 99%
“…It often develops secondary to obstructive pathologies. Although it is rare, it co-exists with dysplastic non-functional kidney on the same side in 80% of cases (11). Urinary ascites develops in cases with lower urinary tract obstruction following to spontaneous or iatrogenic rupture of the kidney or bladder.…”
Section: Urinary System Evaluation With Prenatal Ultrasoundmentioning
confidence: 99%